Evolutionary Perspective of Sulfur Dynamics in Tomohon and Implications on Microbial Corrosion - Frity Lisa Taroreh; Jubhar C Mangimbulude; Ferry F Karwur (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Sulfur (S) is a non-metal, multivalent, tasteless and odorless element. The vast amount of sulfur valence (from S2- to S6+)allows such element to participate in various geochemical and biochemical processes. In nature, sulfur is everywhere, abundant and distribute evenly on earth and the solar system. On ‘ancient’ earth in anoxic atmospheric condition, sulfur existed in the form of H2S. In oxic period, following the discovery of photosynthesis, sulfur was commonly found in the form of sulfur oxides (SOx). This paper discusses the evolutionary perspective of sulfur by presenting and discussing three following aspects: (i) The formation ofsulfur element through “nucleosynthesis” that generating 4 sulfur isotopes with various abundances (32S= 95.02%; 33S = 0.75%; 34S = 4.21%; 36S= 0.02%), (ii) Geological record of ∆33S and sulphate dynamics in the atmosphere since 2,500,000,000-290,000,000 years ago as volcanic gas; and, (iii) The transformation of various types of sulfur compounds in oxic condition nowadays as SO2 , SO3, H2SO4, sulfite salt, sulfate salt, and organic sulfur aerosols.Special attention is given to the sulfur cycle and changing dynamics in nature related to volcanism in geological context of North Sulawesi, especiallyTomohon areas, and practical implication of microbiological corrosion is considered as the implication of the sulphuric evolution that affect the life of modern society.